Parental Attitudes to Genetic Testing Differ by Ethnicity and Immigration in Childhood Nephrotic Syndrome: A Cross-Sectional Study. Issue 1 (17th March 2016) - Borges, Karlota; Vasilevska-Ristovska, Jovanka; Hussain-Shamsy, Neesha; Patel, Viral; Banh, Tonny; Hebert, Diane; Pearl, Rachel J.; Radhakrishnan, Seetha; Piscione, Tino D.; Licht, Christoph P. B.; Langlois, Valerie; Levin, Leo; et al.
Background: Studies in the USA report differences in opinion among parents of different ethnic groups toward genetic testing for their child; however, there are no studies that address this issue in the diverse ethnic and immigrant population in Canada. Objective: This study aims to determine whether ethnicity and immigration status influences parental interest in clinical genetic testing for a potentially progressive kidney disease. Design: This is a cross-sectional study. Setting: Participants were recruited from the Greater Toronto Area, Canada. Participants: The study included 320 parents of children ages 1–18 years with nephrotic syndrome enrolled in the Insight into Nephrotic Syndrome: Investigating Genes, Health and Therapeutics (INSIGHT) observational cohort study. Measurements: Demographic, ethnicity, immigration, and child specific factors as well as interest in genetic testing were collected through self-reported questionnaires administered at baseline study visit. Methods: Logistic regression models were used to examine association of ethnicity and immigration status with interest in genetic testing. Results: The majority of parents (85 %) were interested in genetic testing for their child. South Asian and East/Southeast Asian parents had 74 and 76 % lower odds of agreeing to genetic testing when compared to Europeans (odds ratio (OR) 0.26, 95 % confidence interval (CI) 0.10–0.68; OR 0.24, 95 % CI 0.07–0.79, respectively) after controlling for age and sex of child, age and education level of parent, initial steroid resistance, and duration of time in Canada. Immigrants to Canada also had significantly lower odds (OR 0.29, 95 % CI 0.12–0.72) of agreeing to genetic testing after similar adjustment. Higher education level was not associated with greater interest in genetic testing (OR 1.24, 95 % CI 0.64–2.42). Limitations: Participants have already agreed to aggregate genetic testing for research purposes as part of enrolment in INSIGHT study. Conclusion: While majority of parents were interested in genetic testing for their child, immigrants, particularly South Asians and East/Southeast Asians, were more likely to decline genetic testing. Genetic counseling needs to be tailored to address specific concerns in these parental groups to maximize informed decision-making in the clinical setting. Trial registration: ClinicalTrials.gov, NCT01605266